Migrating a Journal Platform: Stars Wars and a New Future - Regina Raboin (Journal of eScience Librarianship, 2022)
Moving to a new journal platform brings opportunities toevolve services so that users and the publishing team will benefit. There aremany people involved in this type of migration, the vendor, authors who havewaited patiently for their article to be published, but most importantly is theteam who have spent years to make this new platform a reality.